Sorption and Desorption Studies of Lead(II) Using Sawdust as Potential New Sorbent - Ganesan, Thipashini (IRC, 2016)
The presence of heavy metals in the environment is a major problem due to usage as raw material continues to grow with industrial and technological development. This work has examined the sorption and desorption characteristics of Pb(II) on activated carbon prepared from Hevea Brasilinesis, rubber wood sawdust. This studies emphasizes on activated carbon prepared from rubber wood sawdust using different activating agent, impregnation ratio and temperature successfully synthesized, analyzed and evaluated for adsorption and desorption of Pb(II). Surface area analyzer (BET) was employed in order to determine specific surface area and pore size distribution of the prepared activated carbon from chemical modification methods.